Fescue Hay Cost-Return Budget in Central and Eastern Kansas - Fogleman, Sarah L. (My University, 2000)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_2000_10
Keywords: MF2146; Crops; Economics; MF